Implementasi Metode Discovery Learning Menggunakan Field Work Materi Persebaran Flora Di Indonesia Untuk Meningkatkan Kemampuan Psikomotorik Siswa Kelas XI Di MA At Thohiriyah Ngatru Tulungagung - Khisni Kholifatun Nisa; Nur Isroatul Khusna (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this study is to describe the implementation of the discovery learning method using field work to determine students' psychomotor abilities by looking at the steps and supporting factors that inhibit the application of the discovery learning method using field work. This study uses a mixed methods research method. This type of research uses statistical descriptive quantitative and descriptive qualitative. While the qualitative data collection methods used in this study were observation, interviews, and documentation, quantitative research used data collection with questionnaires. The number of respondents is less than 100, so the total population is taken as a sample of 20 students in class XI. Qualitative data analysis in the form of data collection, data reduction, data presentation, and drawing conclusions, while quantitative data analysis uses single tabulations and percentages.